Green synthesized of zinc oxide nanoparticles and calcined biowaste for sustainable electrodes to asymmetric supercapacitors - Ersoy, Serra; Aleinawi, Mohamad Hasan; Erdem, Emre; Kaya, Figen; Kaya, Cengiz; Koc, Bahattin (NATURE PORTFOLIO, 2025)
Green synthesis is increasingly popular due to the focus on sustainability and biowaste recycling. This study explores zinc oxide nanoparticles (ZnO NPs) synthesized using broccoli extract, with carbon powder derived from calcined broccoli pulp as an alternative to commercial carbon in electrochemical slurries. Powders were characterized, and slurries were prepared in a three-electrode system with 6 molar (M) potassium hydroxide (KOH) electrolyte. Results showed that biowaste carbon in 50-70 nm ZnO NPs slurry increased specific capacitance by 74.64 Farad/gram (F/g). The ZnO NPs/biowaste carbon powder retained 64% stability after 500 cycles, with 400 degrees Celsius (degrees C) identified as the optimal calcination temperature for asymmetric supercapacitors. Thanks to this study, the energy applications of materials produced by recycling biowaste in a sustainable and non-toxic way have been examined in detail for the first time.
Keywords: Transition metal oxides; Supercapacitors; Eco-friendly synthesis; Sustainability; Biowaste recycling; CARBON; EXTRACT; Science & Technology - Other Topics